The effect of problem based learning model on critical thinking skill students in primary school - N Fadillah; B Maftuh; E Syaodih (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Critical thinking is one of the 21st century skills that needs to be developed. This skill is one of the most important basic modalities for everyone and can affect their future life. This research aim to obtain a description of the effect of problem based learning on critical thinking skill students of grade IV in one of the primary schools in Lima Puluh Kota district, West Sumatera province. The research adopted quantitative research and employed quasi experiment which is non-equivalent control group design. The subjects of this research were 40 students of class A as an experimental class and class B as a control class. The data were collected through instrument tests which is critical thinking skill test on natural science subjects especially natural resource materials. The result of this research showed that critical thinking skill students in experimental class improved significantly. So, it can be concluded that the problem based learning affect to critical thinking skill students. This research is expected to be a reference of teachers in developing innovative natural science learning, let alone explicitly this concept not only emphasizes the cognitive abilities of students, but also implicitly can develop their social skills in natural science perspective.